Peran literasi keuangan, persepsi risiko, motivasi terhadap minat investasi generasi z di Surabaya - Nadia Rachelita Prameswari; Haryati Setyorini (Universitas Hayam Wuruk Perbanas, 2025)
ABSTRACT Investment interest reflects a person's desire or tendency to invest their capital in financial instruments with the aim of obtaining profits in the future. High investment interest can be supported by financial literacy, risk perception and motivation to determine appropriate investment instruments. This research aims to explore whether there is an influence of the variables financial literacy, risk perception and motivation on investment interest. The sampling technique uses a non-probability sampling technique, namely purposive sampling. This research used 143 respondents from Generation Z with an age range of 17 to 27 years who live in the city of Surabaya. The data analysis technique uses the SEM (Structural Equation Modeling) method using SmartPLS-4.0 statistical software. The results of this research show that the financial literacy variable is proven to have a significant positive effect on investment interest. Furthermore, the motivation variable is proven to have a significant positive effect on investment interest. However, the risk perception variable was not proven to have a significant effect on investment interest. Based on the results of this research, prospective investors can increase their education about risk management so that prospective investors can be wiser and more informed to increase interest in investing.